Quality and Diagnosis on the Lateral View of Pediatric Upper Gastro-Intestinal Series - Shyam Sunder B. Venkatakrishna; Mohamed Elsingergy; Juan S. Calle-Toro; Rebecca Dennis; Hansel J. Otero; Savvas Andronikou (MDPI AG, 2024)
Background: The standard imaging technique for the diagnosis of intestinal malrotation remains the upper gastro-intestinal series (UGIS). The lateral view is promoted as important for making a diagnosis. For this, the lateral view should be of adequate quality, and radiologists must know the normal appearance as well as the appearance of duodenal variants, as misdiagnosis may lead to unnecessary surgery. Objective: We aimed to evaluate the quality, findings including the prevalence of the "descending staircase" configuration and its correspondence to a diagnosis of duodenum redundum. Materials and Methods: This was a retrospective study and was conducted in a large tertiary children's hospital in the United States. A retrospective review of UGI fluoroscopy exams in children aged ≤ 18 years between January and December 2018 was performed by a pediatric radiologist. First, the lateral view images/cine-loops were assessed independently, followed by the anteroposterior (AP) view. The studies which were designated to have an adequate lateral view were evaluated for configuration of the duodenum and recorded as: normal, abnormal, or normal variant. Also, the presence of a descending staircase configuration was correlated with an AP view for a diagnosis of duodenum redundum. Results: A total of 26 children (26%) (males:16; females:10) with age range 0 to 16 years had adequate lateral views during UGI exams for inclusion. Of the 26, 18 (69%) were reported as normal, 7 (27%) were reported as having a descending staircase and 1 (4%) was reported as abnormal. The AP view demonstrated 2 abnormal studies (1 malrotation and 1 non-rotation), 6 duodenum redundum and 18 normal exams. The one abnormal lateral duodenum was confirmed as a non-rotation on AP view; the second patient with an abnormal AP view had a normal appearance on the lateral view. Conclusions: A total of 26% of UGI studies had adequate lateral views for interpretation. Of these, nearly a quarter (23%) demonstrated the descending stair-case sign corresponding to a diagnosis of duodenum redundum on the AP view. If the lateral view had been used alone, there would have been a missed diagnosis in one patient.